A praat-based stuttering analysis of the main character in the king’s speech movie: a neuropsycholinguistic study - Yonnie Kharismadewi; Ike Revita; Rina Marnita AS (Journal of Applied Studies in Language, 2023)
Stuttering is a speech disorder characterized by involuntary repetitions or prolongations of words or syllables, or by involuntary interruptions in the flow of speech, known as blocks. Stuttering can happen due to genetics and environmental factors or psychogenic. This research aims to identify the types of stuttering that occur and to explain the factors that contribute to stuttering and the effect on the main character's speech fluency in the movie "The King's Speech." The data for this research comes from The King's Speech movie. The descriptive qualitative approach was used in this study in which the method and technique used in collecting the data were the observation method and the technique consists of observing, recording using Praat as a speech analyzer, and noting. The data were analyzed using the referential and distributional methods. Based on the result of the data analysis, the number of data for the type of stuttering is 286 data, each of them consisting of 158 data for repetition, 124 data for blocking, and 4 data for prolongation. In analyzing Bertie’s utterance, Bertie, as the main character, found a problem in producing consonants that cause stuttering, the consonants consist of /m/, /k/, /b/, /p/, /y/, /ch/, /th/, / c/, /g/, /w/ , /h/, /f/, /n/, /d/, and /s/ with repetition of sounds in words starting with phonemes /m/, /p/, /k/ and /b/ predominates when stuttering occurs. Meanwhile, the repetitions of vowel sounds that often occur are /a/, /i/, /o/, /e/ and the vowel sounds /a/ and /i/ dominate each repetition sound. Besides the problem in producing consonants and vowels in utterance, psychological factors are also the main factors in the occurrence of stuttering, such as feelings of depression, anger, and anxiety that trigger the main character to produce speech-blocking. Therefore, the type of stuttering experienced by the main character is psychogenic stuttering.